A study on factor that influence job satisfaction of employees in private sector: a case study at Aero Composite Technology Sdn Bhd / Rokiah Faroog Ahmad - Faroog Ahmad, Rokiah (2003)
Job satisfaction has always been important issue nowadays. It may determine the successful and the failure of the organization. It means that organization can sustain their performance when they have employees with high job satisfaction. Therefore, this study is to examine the factors that contribute to job satisfaction among the employees in ACT. Samples of 50 employees were interviewed. This study tries to find the relationship employees job satisfaction with demographic factor (age, gender, tenure, marital status, education, position) workplace environment, salary, supervision, recognition and work itself and other variables. Instead of interviewing and self-administered questionnaires, other method research that have been used in this study are data collection, cluster sampling technique, and also Statistical Package for Social Sciences (SPSS). This finding is hopefully can contribute and help the Human Resource Department in Aero Composite Technology in order to upgrade their level of employees job satisfaction.